THE INFLUENCE OF IMPLEMENTING THE INDEPENDENT LEARNING CURRICULUM ON ECONOMICS LEARNING OUTCOMES OF CLASS X STUDENTS OF DWIWARNA PRIVATE HIGH SCHOOL MEDAN T.A 2023/2024 - Kristina Nainggolan; Rijal; Zulkifli Hasibuan; Samio (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to determine the effect of implementing the independent learning curriculum on the economic learning outcomes of class X SMAS Dwiwarna Medan T.A 2023/2024 students. This research is quantitative research. The research location is SMAS Dwiwarna Medan. The sampling in this study amounted to 16 respondents. The data collection technique in this research uses a questionnaire method and a set of economic material test questions. The results of this research show that the implementation of the independent learning curriculum at SMAS Dwiwarna Medan is in fairly good condition, the results show that the mean (average) of variable 80). This means that the effect of implementing the independent learning curriculum with moderate qualifications is to influence learning outcomes. And the students' economic learning outcomes are classified as very good. The average value of economic learning outcomes for SMAS Dwiwarna Medan students is on average 51-70 for 16 students, namely 56.25% of the total sample. Why 51-70 because there are 30 multiple choice questions for SMAS Dwiwarna Medan students. This means that the average student learning outcomes or the majority of students including graduate qualifications are very good. Based on data analysis that is in accordance with hypothesis testing in research using the biserial correlation test with the result of the significance value of data testing being -478 which has a very strong relationship, and in testing using the T test the t-count result obtained is 0.57716 which is greater than t -table of 0.28858 (0.57716>0.28858) (tcount falls on rejection of Ho). So it can be concluded that Ho is rejected and Ha is accepted, which means that there is